Targeting β-glucans, vital components of the Pneumocystis cell wall - Wang, Mengyan; Zhang, Zhongdong; Dong, Xiaotian; Zhu, Biao (Frontiers in Immunology, 2023)
β-glucan is the most abundant polysaccharide in the cell wall of Pneumocystis, which has attracted extensive attention because of its unique immunobiological characteristics. Its immune effect is attributed to the ability to bind with different receptors expressed on the different cell surface resulting in inflammatory response. A better understanding of the mechanisms of Pneumocystis β-glucan recognition, downstream signaling pathways, and subsequent immune regulation activation is essential. It can provide a basis for developing new therapy of Pneumocystis. Here, we briefly review the structural composition of β-glucans as a vital component of the Pneumocystis cell wall as well as host immunity mediated by β-Glucans after their recognition, and discuss how to open opportunities for the development of new strategies to combat Pneumocystis.